Design and Development of Energy Particle Detector on China’s Chang’e-7 - Liping Wang; Guohong Shen; Huanxin Zhang; Donghui Hou; Shenyi Zhang; Xianguo Zhang; Zida Quan; Jiajie Liao; Wentao Ji; Ying Sun (Aerospace)
Particle radiation on the Moon is influenced by a combination of galactic cosmic rays, high-energy solar particles, and secondary particles interacting on the lunar surface. When China’s Chang’e-7 lander lands at the Moon’s South Pole, it will encounter this complex radiation environment. Therefore, a payload detection technology was developed to comprehensively measure the energy spectrum, direction, and radiation effects of medium- and high-energy charged particles on the lunar surface. During the ground development phase, the payload performance was tested against the design specifications. The verification results indicate that the energy measurement ranges are 30 keV to 300 MeV for protons, 30 keV to 12 MeV for electrons, and 8 to 400 MeV/n for heavy ions. The energy resolution is 10.81% for 200 keV electrons of the system facing the lunar surface; the dose rate measurement sensitivity is 7.48 µrad(Si)/h; and the LET spectrum measurement range extends from 0.001 to 37.014 MeV/(mg/cm2). These comprehensive measurements are instrumental in establishing a lunar surface particle radiation model, enhancing the understanding of the lunar radiation environment, and supporting human lunar activities.